Acceptance of human papilloma virus self-testing in cervical cancer prevention among rural Nigerian women - Kerry, Matilda; Okafor , Ifeoma; Roberts, Alero; Balogun, Mobolanle; Oyadotun, Omolara; Opeyemi, Awofeso; Igwilo, Uzoamaka; Olubodun, Tope Olubodun; Akinsulire , Damilola; Igwilo , Ugonna Igwilo (Archive of Oncology, 2026)
Background: This study investigates the knowledge and acceptance of human papillomavirus (HPV) self-testing among rural women in Badagry, Lagos State, Nigeria, aiming to address the growing public health concern of cervical cancer. With 9,922 new cervical cancer cases annually in Nigeria, late diagnosis and suboptimal treatment contribute to high mortality rates. Methods: The study involved 220 women who performed HPV self-sampling alongside physician-conducted visual inspection with acetic acid (VIA) and reported preference. Results: The results reveal inadequate cervical cancer awareness (55.5%) and low HPV knowledge (20.9%), particularly among women with incomplete education. While 80.9% of women preferred VIA, only 49.1% found HPV self-sampling feasible. Notably, self-testing was more accepted among divorced, separated, and widowed women.Conclusion: The efforts to improve education and awareness about the causative role of HPV in cervical cancer awareness are crucial to enhance its utilization and acceptance in rural settings.
Keywords: Papillomavirus Infections, Public Health, Self-Examination, Uterine Cervical Neoplasms, Rural Population, Africa South of the Sahara